Comparative Analysis of Multidisciplinary Complementary Intervention Versus Routine Physiotherapy Rehabilitation to Reduce Kinesiophobia in Patients with Knee Osteoarthritis Undergoing Total Knee Replacement: A Systematic Review and Meta-Analysis - Hung Tzu-Han; Liu Mei-Chun; Kuo Ya-Wen; Lee Jiann-Der (Sports Medicine - Open)
Abstract Background Knee osteoarthritis is a highly prevalent disease that affects 24–31.8% of patients who undergo total knee replacement (TKR); it impedes their rehabilitation and increases their risk of complications. The aim of this systematic review was to compare the effectiveness of multidisciplinary care intervention with that of conventional physical therapy in mitigating kinesiophobia in patients with knee osteoarthritis undergoing joint replacement. Methods This study was registered with the International Prospective Register of Systematic Reviews (registration no. CRD42022366356). Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, two Chinese databases (the National Digital Library of Theses and Dissertations and Airiti Library) and four English databases (CINAHL, Cochrane Library, PubMed, and Embase) were searched from their inception up to January 2023 for randomized controlled trials (RCTs) on multidisciplinary intervention for kinesiophobia following TKR. Results Seven RCTs comprising 648 individuals (327 in the experimental group and 321 in the control group) were included in the analysis. Grading of Recommendations, Assessment, Development, and Evaluations revealed moderate evidence quality and strong recommendations for kinesiophobia, pain, and knee joint functional scales. Meta-analysis revealed that multidisciplinary care intervention significantly outperformed conventional physical therapy in terms of reducing kinesiophobia (P < 0.01), with this effect persisting for up to 6 months after the intervention. The overall effect size (standardized mean difference = -2.57, 95% confidence interval [-3.71, -1.44], P < 0.00001) was large, and no risk of publication bias was found. Conclusions Multidisciplinary care intervention reduces kinesiophobia in patients with knee osteoarthritis following TKR. It also reduces their pain scores and promotes early postoperative ambulation. Two studies of the seven included RCTs had small sample sizes (fewer than 100 individuals); this may have affected the robustness of the findings.